Then comes seduction - Balogh, Mary (Dell, 2009)
In a night of drunken revelry, Jasper Finley, Baron Montford, gambles his reputation as London's most notorious lover on his ability to seduce the virtuous Katherine Huxtable. For Katherine, Jasper's offer is irresistible: to make London's most dangerous rake fall in love with her. Then Jasper suddenly ups the ante by asking her to become his wife.